Transcriptome and apoptosis analysis of feline infectious peritonitis virus-infected crandell rees feline kidney cells - Harun, Mohammad Syamsul Reza (2012)
Feline infectious peritonitis (FIP) is a lethal systemic disease caused by FIP virus (FIPV), a virulent mutant of apathogenic feline enteric coronavirus (FECV). There are no effective diagnostic, vaccine and treatment available because the virus virulence determinants and pathogenesis are not fully understood. This study aims to elucidate the early host genes and the phenomenon of apoptosis associated with in vitro infection of FIPV in cell culture. RNA samples from FIPV serotype II strain 79-1146 infected Crandell Rees Feline Kidney (CRFK) cells at 3 hours post infection were sequenced using Illumina™ next generation sequencer platform then subsequently analysed with CLC bio Genome Workbench software. Sequencing reads were mapped to Felis catus 2X annotated shotgun reference genome and control versus infected cell reads expression analysis was conducted. Kal’s Z test on expression proportions was used to determine significantly expressed genes. Genes expressed with false discovery rate (FDR) less than 0.05 and more than 1.99 fold change were considered for further analysis. RNA-seq analysis mapped both control and infected cell reads to 18899 genes out of 19046 annotated, while expression analysis revealed 61 genes were differentially expressed by both samples with 44 genes were up regulated while the rest were down-regulated. Among the genes is a chemokine for attracting monocytes, CCL8 that was expressed only in infected sample suggesting that early response against FIPV involves cell mediated immunity (CMI). In addition, 4 genes (CXCL10, PHF11, ATF3, IRF1) that associated with Th1 cytokines secretion were also up regulated in this study. Meanwhile, anti-apoptotic gene RNF7 and ribosomal gene RPL39 were expressed only in control sample indicating that FIPV initiate apoptosis and disturb host cell protein translation as early as 3 hours after infection. Besides that, 9 pro-apoptotic genes (CXCL10, MX1, RSAD2, UBA7, RNF19B, ESE1,BAK1, CASP7, PD-L1) were up regulated while another 3 anti-apoptotic genes (c-Kit, CKS2, ID-1) were down regulated. The detail role of those genes and other differentially expressed genes are discussed. The ability of the virus to induce apoptosis in CRFK cells was also analysed within 48 hours at 12 different time frames which are 3, 9, 12, 15, 18, 21, 24, 27, 30, 36, 42 and 48 hours by flow cytometry and annexin-V FITC staining. Apoptosis analysis confirmed that a significant number of cells undergo early apoptosis 18 hours post-infection and late-apoptosis 30 hours post-infection. This study has succesfully identified several candidate genes that may play important role in FIPV pathogenesis and has characterized important events in cell death following FIPV infection in CRFK cells.